Investigating the role of miRNA-mediated regulation in antipsychotic treatment response in a South African first-episode schizophrenia cohort - Hamilton, Megan April (Stellenbosch : Stellenbosch Univerity, 2020)
Thesis (MScAgric)--Stellenbosch University, 2020.